The Relationship between Burden and Quality of Life for Caring for Stroke Patients - Islami Yusa, Bunga; Satriawan, Nofri (Dinasti Health and Pharmacy Science, 2023)
This study aims to determine the relationship between burden and quality of life of stroke caregivers at the Bukittinggi National Stroke Hospital Polyclinic. This type of research is analytic research with a cross sectional approach. The analysis used in this study uses univariate analysis and bivariate analysis. The results of the study are 1. Less than half of the caregivers have a moderate burden in caring for stroke patients. 2. More than half of caregivers have a poor quality of life. 3. There is a relationship between the burden and the quality of life of stroke caregivers.